PENGARUH PEMBELAJARAN BERDIFERENSIASI TERHADAP HASIL BELAJAR MATEMATIKA SISWA SEKOLAH DASAR - Nazilatun Sabarikun; Heru Purnomo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The purpose of this research is to improve student learning outcomes in mathematics by using differentiated learning with the subject of geometry (triangles, quadrilaterals, and polygons). This research was conducted at SDN Bikatuk in class IV. This study uses a qualitative descriptive research technique with structured interview techniques, documentation, and observation. The results of the research carried out on 21 students obtained a completeness score in learning mathematics in cycle I of 66.67% with a total of 14 students and students did not meet the passing standard with a percentage of 33.33% with a total of 7 students. Then in cycle II the completeness of the lesson results students' mathematics with an acquisition of 80.96% with a total of 17 students and students who have not met the graduation requirements of 19.04% with a total of 4 students. This research shows that the application of differentiated learning can increase students' knowledge in mathematics. This can be seen from the significant improvement in students' learning outcomes in mathematics between the first and second cycles.